Redefine Sustainable Fisheries Targets Under the Impact of the Southern Yellow Sea Green Tide: Mitigating the Recurring Surge in Natural Mortality - Sun, Ming; Li, Yunzhou; Ren, Yiping; Chen, Yong (Frontiers in Marine Science, 2022)
The massive green tide blooms caused by macroalgae Ulva in the Southern Yellow Sea, China, threaten the local fish populations. However, green tides are not factored into the determination of sustainable fisheries targets, which hinders the achievement of the maximum sustainable yield (MSY). Using a local fishery as a case study we highlighted the need to redefine the MSY-based targets in the face of green tides. We modeled the green tide blooms as natural mortality events and evaluated their effects on fisheries with the “green-tide-free” sustainable fishing intensity FMSY. We then recalculated these targets by accounting for the surges in natural mortality. We found that green tides caused at least 10% losses in biomass and catch when unaccounted for. Additionally, FMSY must be reduced by 4–8% to achieve MSY in the face of the green tide, which was approximately 20% lower than the “green-tide-free” value, indicating the damages of green tides could be partially mitigated.